Application of Light Color and Lighting Height on the Growth and Yield of Chrysanthemum Cut Flowers (Dendranthema grandiflora Tzelev) - Yeo Vinco; I Gusti Bagus Udayana; Made Sri Yuliartini; I Gusti Made Arjana Arjana; Ni Luh Putu Sulis Dewi Damayanti; Ni Kadek Desy Andya Dewi (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Chrysanthemum is a highly valuable commercial cut flower. Providing supplemental lighting at an optimal height is crucial to enhancing plant growth and flower quality. This study evaluated the effects of light color, lighting height, and their interaction on the growth and yield of chrysanthemum (Dendranthema grandiflora). The experiment was conducted in a greenhouse at Agro Pudak Lestari Farm, Buleleng, Bali, utilizing a factorial Randomized Block Design (RBD) with two factors: light color (white [Wp], purple [Wu], and yellow [Wk]) and lighting height (1 m [T1], 2 m [T2], and 3 m [T3]), replicated three times. Although the interaction between the two factors had no significant effect on any of the observed variables, each factor individually exhibited significant to highly significant effects. Yellow light (Wk) yielded superior plant growth, stronger stems, enhanced visual quality, and the highest economic fresh weight at 77.91 g—a 30.9% increase compared to white light (Wp). Meanwhile, a lighting height of 2 meters optimized growth variables by 4.7–7% and increased economic fresh weight by 15.1%. Consequently, applying yellow light at a height of 2 meters is highly recommended to maximize the growth and yield of chrysanthemum cut flowers. Contribution to Sustainable Development Goals (SDGs):SDG 8: Decent Work and Economic GrowthSDG 9: Industry, Innovation, and Infrastructure